Understanding the molecular mechanisms of human microtia via a pig model of HOXA1 syndrome - Ruimin Qiao; Yuyong He; Bo Pan; Shijun Xiao; Xufei Zhang; Jing Li; Zhiyan Zhang; Yuan Hong; Yuyun Xing; Jun Ren (The Company of Biologists, 2015)
Microtia is a congenital malformation of the outer ears. Although both genetic and environmental components have been implicated in microtia, the genetic causes of this innate disorder are poorly understood. Pigs have naturally occurring diseases comparable to those in humans, providing exceptional opportunity to dissect the molecular mechanism of human inherited diseases. Here we first demonstrated that a truncating mutation in HOXA1 causes a monogenic disorder of microtia in pigs. We further performed RNA sequencing (RNA-Seq) analysis on affected and healthy pig embryos (day 14.25). We identified a list of 337 differentially expressed genes (DEGs) between the normal and mutant samples, shedding light on the transcriptional network involving HOXA1. The DEGs are enriched in biological processes related to cardiovascular system and embryonic development, and neurological, renal and urological diseases. Aberrant expressions of many DEGs have been implicated in human innate deformities corresponding to microtia-associated syndromes. After applying three prioritizing algorithms, we highlighted appealing candidate genes for human microtia from the 337 DEGs. We searched for coding variants of functional significance within six candidate genes in 147 microtia-affected individuals. Of note, we identified one EVC2 non-synonymous mutation (p.Asp1174Asn) as a potential disease-implicating variant for a human microtia-associated syndrome. The findings advance our understanding of the molecular mechanisms underlying human microtia, and provide an interesting example of the characterization of human disease-predisposing variants using pig models.